Down to Earth: The Future of the Flint Hills - Jim Sherow (Symphony in the Flint Hills, 2016)
What is the future of the Flint Hills? A historian, provides important insights about future trends.
Keywords: down to earth; historian; future trends; past; future; AQUIFER; Bill McBride; DAWN AND DUSK; Shin-hee Chin; GRAIN ELEVATOR; Phil Epp; DRAGONFLY; HUMMINGBIRD; RAVEN; Hilary Lorenz; GREEN JUNGLE